(untitled) (Szociológiai Szemle, 2023)
The article examines the movement of grassroots organizations and volunteers in Hungary that suddenly emerged during the European migration and refugee crisis in 2015. This movement emerged in a society with low level of trust and high level of xenophobia, without any relevant previous examples. This movement was built from scratch via Facebook groups and provided humanitarian aid for the refugees and migrants on streets and railway stations of major cities in Hungary as a response to the lack of sufficient aid by the official relief organizations and the state. The analysis is based on various qualitative data sources and covers the motivational structure of the volunteers and grassroots organizations, their operational methods, including the nature of cooperation and conflicts that emerged during relief work. In addition, the article also deals with the attitudes and (the lack of) activity of the established charities and other NGOs. The study reflects on the political context and the public debates and also analyses the role of online and social media during the migration crisis, focusing on the summer and fall of 2015.